2021
DOI: 10.4047/jap.2021.13.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional finite element analysis of buccally cantilevered implant-supported prostheses in a severely resorbed mandible

Abstract: PURPOSE The aim of the study was to compare the lingualized implant placement creating a buccal cantilever with prosthetic-driven implant placement exhibiting excessive crown-to-implant ratio. MATERIALS AND METHODS Based on patient's CT scan data, two finite element models were created. Both models were composed of the severely resorbed posterior mandible with first premolar and second molar and missing second premolar and first molar, a two-unit prosthesis supported by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Uniform distribution in the rest of the abutment body (Figure 3.c). The experimental group showed 875.63 MPa and was 28% greater than the control group (683.88 MPa), a result similar to that of Alom et al (2021), who, when analyzing a buccal cantilever in a single prosthesis, found greater stress in the abutment of the group tested.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Uniform distribution in the rest of the abutment body (Figure 3.c). The experimental group showed 875.63 MPa and was 28% greater than the control group (683.88 MPa), a result similar to that of Alom et al (2021), who, when analyzing a buccal cantilever in a single prosthesis, found greater stress in the abutment of the group tested.…”
Section: Discussionsupporting
confidence: 82%
“…Planning for implant installation is essential, however, often due to anatomical limitations such as pronounced resorption of the maxillae and consequent approximation of important structures such as the maxillary sinus, nasal fossa, mentual foramen and even the inferior alveolar nerve, This procedure aims to simplify planning, thus avoiding extensive surgeries, minimizing costs and morbidity (Alom et al, 2021;da Silva et al, 2018;Manea et al, 2019;Muangsisied et al, 2021).…”
Section: Discussionmentioning
confidence: 99%